Germination, seed diameter and pregerminative treatments in species with different purposes of use - Abril-Saltos, Ricardo Vinicio; Ruiz-Vásquez, Tomás Elías; Alonso-Lazo, Jatnel; Cabrera-Murillo, Génova Marjorie (Agronomía Mesoamericana, 2017)
The evaluation of vegetal species germination consents to know its characteristics and permits to understand the factors that influence this process. The aim of this research was to know the germination’s characteristics of some species, such as Eugenia stipitata McVaugh, Inga edulis Mart, Inga spectabilis (Vahl) Wild, Piptocoma discolor (Kunth) Pruski, Stachytarpheta cayennensis (Rich.) Vahl, and Verbena officinalis L., and also their reaction to pregerminative treatments depending on the seed’s diameter. This study was carried out in Pastaza, Province of Pastaza, Ecuador, between February and June, 2014. Different diameters of seeds and pregerminative treatments were used in species, which did not present germination percentages higher than 40%. In the first practice I. edulis and I. spectabilis exceeded this value without treatment. Other species had lower values. Seeds were classified considering two diameters and two doses of gibberellin acid, this was applied to, and evaluated in the E. stipitata. In addition, scarification with sulfuric acid was done. After 45 days of its application, 100 ppm of gibberellic acid with larger seed diameter reported higher percentages of germination in S. cayenennsis, and in E. stipitata, which also interacted with the scarification. V. officinalis and P. discolor, did not present any response to the applications made. I. edulis and I. spectabilis presented high germination percentages without pregerminative treatments, E. stipitata and S. cayenennsis showed response to seed diameter and the applied treatments, while P discolor and V. officinalis did not show any response.